2016
DOI: 10.1111/febs.13921
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional start site turnover in the evolution of bacterial paralogous genes – the pelE‐pelD virulence genes in Dickeya

Abstract: After a gene duplication event, the resulting paralogous genes frequently acquire distinct expression profiles, roles, and/or functions but the underlying mechanisms are poorly understood. While transcription start site (TSS) turnover, i.e., the repositioning of the TSS during evolution, is widespread in eukaryotes, it is less documented in bacteria. Using pelD and pelE, two closely related paralogous genes encoding key virulence factors in Dickeya, a gamma proteobacterial genus of phytopathogens, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…While the maceration enzyme arsenal is quite similar in Ddi04.9 and Dso3337, most of the encoded genes were equally or even more expressed in Ddi04.9 than in Dso3337, with the exception of pelE . Interestingly, PelE plays a key role in the initiation of maceration by Dickeya (Duprey et al ., ). This noticeable difference in pelE expression levels could contribute to the stronger capacity of Dso3337 to initiate maceration at a low cell density, as we showed in this work.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While the maceration enzyme arsenal is quite similar in Ddi04.9 and Dso3337, most of the encoded genes were equally or even more expressed in Ddi04.9 than in Dso3337, with the exception of pelE . Interestingly, PelE plays a key role in the initiation of maceration by Dickeya (Duprey et al ., ). This noticeable difference in pelE expression levels could contribute to the stronger capacity of Dso3337 to initiate maceration at a low cell density, as we showed in this work.…”
Section: Discussionmentioning
confidence: 86%
“…Remarkably, pelE is the unique pel gene that is more expressed in Dso3337 than in Ddi04.9 in tuber colonizing condition and it is also about 10‐fold more expressed in rich medium in Dso3337 than in Ddi04.9. Because this gene plays a key role in the initiation of maceration by Dickeya (Duprey et al ., ), we hypothesized that Dso3337 could more efficiently initiate maceration than Ddi04.9. To test this hypothesis, tubers were infected by a low cell number (2 × 10 4 CFU per tuber), and after 5‐days incubation, the measured symptoms were stronger following Dso3337 infection than that of Ddi04.9.…”
Section: Resultsmentioning
confidence: 97%
“…S2), suggesting that strain ATCC 39006 represents the sisterlineage of Dickeya, and was wrongly affiliated to the Serratia, based on its capacity to synthesize prodigiosin, a red pigment secondary metabolite with antimicrobial, anticancer and immunosuppressant properties, characteristic of Serratia species (Thomson et al, 2000). The sisterrelationship of ATCC 39006 and Dickeya is consistent with the close evolutionary link between the pectinolytic gene clusters (pel, paeY and pemA) shared by these taxa (Duprey et al, 2016b), and with the presence, in Serratia sp. ATCC 39006, of an homologue of the Vfm quorum sensing system previously reported as specific to Dickeya species (Supporting Information Table S4 and Fig.…”
Section: Deciphering the Early Evolution Of Dickeyamentioning
confidence: 78%
“…According to their taxonomic distribution and phylogeny, most of these proteins could be inferred in the ancestor of Dickeya and in its sister lineage P. confusarubida . Regarding the pelAED cluster, while P. confusarubida has a single gene, the ancestor of Dickeya had two copies, pelA and an undifferentiated pelDE pectate lyase‐coding gene (Duprey et al ., ), suggesting that a duplication event occurred in the stem of Dickeya . This undifferentiated pelDE has undergone a duplication event after the emergence of D. paradisiaca , giving rise to pelD and pelE (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1D, 1E and 1F). A recent study demonstrated that the transcriptional start site shift after gene duplication might be one of the reasons for the different expression patterns of pelD and pelE (Duprey et al , 2016). However, the upstream regulatory mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%